2021
DOI: 10.3390/w13212998
|View full text |Cite
|
Sign up to set email alerts
|

Operation and Performance of Austrian Wastewater and Sewage Sludge Treatment as a Basis for Resource Optimization

Abstract: Recent years came with a paradigm shift for wastewater treatment plants (WWTPs) to extend the sole purpose of contaminant removal to an additional function as resource recovery facilities. This shift is accompanied by the development of new European legislation towards better inclusion of resource recovery from wastewater. However, long operational lifespans and a multitude of treatment requirements demand thorough investigations into how resource recovery can be implemented sustainably. To aid the formulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…Filter pressing generally yields TS contents between 15 and 25%; approximately 73% of the reported data ( n = 78) fall within this range. The observed data are similar but not identical to the data collected in Austria by Amann et al (2021) , who observed from 238 datasets (no information on sludge type was available), median TS contents of 28% for filter presses, 25% for centrifuges and 24% for screw presses.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Filter pressing generally yields TS contents between 15 and 25%; approximately 73% of the reported data ( n = 78) fall within this range. The observed data are similar but not identical to the data collected in Austria by Amann et al (2021) , who observed from 238 datasets (no information on sludge type was available), median TS contents of 28% for filter presses, 25% for centrifuges and 24% for screw presses.…”
Section: Resultssupporting
confidence: 77%
“… González et al (2017) used multivariate analysis to characterise SS in Andalusia, Spain, while Mailler et al (2017) provided data on emerging and priority micropollutants in SS in Paris, France, and the heavy metal content of SS was described by Mulchandani and Westerhoff (2016) and Fijalkowski et al (2017) . Other papers have focused on composition change during sludge treatment: Thomsen et al (2017) reported its composition after pyrolysis, gasification and incineration; Lemée et al (2017) addressed organic matter changes during drying, irradiation and anaerobic digestion, and Pastor et al (2008) , Egle et al (2016) , Cieslik and Konieczka (2017) and Amann et al (2021) focused on the content and recovery of phosphorus. These case-specific data showed high variation in sludge parameters, with various sources, preprocesses, analyses and inherences.…”
Section: Introductionmentioning
confidence: 99%
“…The activated sludge is partially recycled, whereas the sludge bleed is concentrated with a belt filter. Since an absence of toxic compounds was considered, additional processing was deemed unnecessary and a sludge disposal cost of 10 USD per metric ton (Mton) was taken into account [31]. Finally, the treated water is passed through a granular media filter to remove solid particles [28].…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…In the future, 65-85% of sewage sludge is intended to be brought to phosphorus recovery from incineration ash. Still, detailed planning of the corresponding infrastructure and assessment of different options for phosphorus recovery considering costs and possible environmental impacts are necessary [72,96]. To utilize the energy recovery potential, integrating spatial planning and targeted participation of stakeholders to broaden awareness and acceptance of wastewater as energy source appear to be crucial [87,97].…”
Section: Status Quo Of Target 63 In Austriamentioning
confidence: 99%